BENTUK DAN FUNGSI DEIKSIS DALAM KOMIK TINTIN: LE SCEPTRE D'OTTOKAR - Rahmawati, Desi (Diksi, 2020)
(Title: Deixis Form and Function on Tintin Comic's: Le Sceptre D'ottokar). This study aim to identify deixis form and describe function of deixis lexicons on Tintin: Le Sceptre d'Ottokar (T.LSO). The data were gathered through observation, as the basic technique was tapping technique. Then it was  followed by Uninvolved Conversation Observation Technique and combined with record technique. The data analysis that used are referential [identity] method.The results of the study show that: 1) symbolic deixis has referential function, conative function and emotive function, 2) gestural deixis de la tíªte: un objet, un lieu et une personne is not found, 3) gestural deixis désigne de la main/ pointage has referential and conative function, 4) gestural deixis du regard has referential and emotive function, 5) anaforic deixis has referential and conative function. Keywords: deixis, comic, pragmatic